Geomorphological study of the rock-slope failure at Adjet, Storfjord, Troms - Nopper, Hannah (UiT Norges arktiske universitet, 2015)
Norway is known for its steep mountains and many fjords. This landscape provides the potential for large rock-slope failures (RSFs) which, in turn, can cause other catastrophic hazards, e.g. tsunamis. In Troms County, northern Norway, many RSFs are found east and west of the Lyngen peninsula, within an area of discontinuous permafrost. The RSF at Adjet is located southeast of the Lyngen peninsula. It is not a hazard for people as such, but it is of interest for better understanding RSFs in general, due to its complexity. The aim of the present study is to gain an understanding of the rock-slope failure at Adjet, its geomorphological features, and the origin and movement of these features. The features were identified and analyzed using different methods such as field mapping, evaluation of aerial and orthophotographs, as well as InSAR data. The investigated RSF area is situated on a west facing mountainside, 500 – 1340 m a.s.l., with a ca. 5 km long ridge delimiting the RSF area to the east. The downslope length of the RSF is ca. 2 km. The failure site is of great size and complexity and contains several different geomorphological and structural features. The predominant lithology is mica schist with various amounts of garnet and/ or quartz. The mountain ridge character above the RSF changes from north to south, from a peak-like ridge and cliffs to a relatively gradual sloping ridge. The study area can therefore be divided into two provinces: province A in the north and province B in the south. These provinces are separated by an ENE-WSW trending fault. Geomorphological features within the RSF area are rock glaciers, debris fields, talus fan deposits, and slide blocks. They originate through different failure processes, such as rockfall, toppling and rock slide. In province A, mainly rock glaciers and debris fields are prominent. In province B, slide blocks and talus fan deposits are dominant features. The source of the rock-slope failure is the mountain wall. Folds, faults and fractures are identified, and ...